Reverberações midiáticas de um acontecimento : o caso Isabele em Cuiabá - Santos, Beatriz Alves dos (2023)
The following work presents and analyzes the framing given by Globo program Fantástico to the case of the murder of 14-year-old teenager Isabele Guimarães in Cuiabá- Mato Grosso. The teenager's death took place in July 2020 and had national repercussions. The shot that took Isabele's life was carried out by her then friend of the same age in an upper-class neighborhood. The case was presented in a series of six reports and was followed from the beginning to the end of the investigations and convictions. The work presented here is divided into four chapters, on the first there is a complete presentation of the case; on the second, the main studies on the operator concept - framing, and the concepts of event and relational paradigm are explained; also bringing theoretical contributions to television discourse. The third chapter dedicated to methodological procedures presents the concept of Performance and information about the program presented, as well as a brief explanation of the selection and selected reports. In the fourth chapter, we analyze the research findings and examine the second life of the event, contextualizing it with the social issue that intersects it, the pro-armament policy of the federal government at the time. The analyzes and results are constructed between these subdivisions, leaving in the second chapter the operational concept of framing through the work of Erving Goffman (1996) together with the contributions of Robert Entman (1993), Mauro Porto (2004) and Anabela Gradim (2001). The foundation of the theoretical axis - the relational idea of communication is presented by Vera França (2001); the contextualization of the communicative process with the notion of event, are reflected in the work of Louis Quéré (2012). Vera França also contributes to the work in discussions about television discourse together with Suzana Lopes (2017), Guilherme Rezende (2010) and Michele Negrini (2010). In the research findings, fourth chapter, culminating in the Isabele Guimarães case and the second life of the Louis Quéré event (2012), we present the contributions of Ricardo Mendonça and Débora Santos (2009) and the highlights of the deliberative term. Thus, the work also presents which values cross/form this “wave” of media reverberation and, as a result, how the vehicles question their audiences and the power relations that emerge from the tension between the families of the victim and the accused.